Analyzing the Challenges and Opportunities in the Tannery Industry Supply Chain Management in Bangladesh (Global Journal of Management and Business Research, 2024)
This research was conducted in the Tannery Industry in Bangladesh about supply chain management research methods using qualitative and qualitative methods In this case study researchers are gathering information via observation speaking with business owners academics and knowledgeable tanneries and conducting in-depth interviews In this research paper investigates the complexities and dynamics of the tannery industry supply chain in Bangladesh It examines the strengths weaknesses opportunities and threats within the industry along with an in-depth analysis of the critical supply chain management problems that hinder its efficiency and sustainability By identifying these challenges the research aims to propose viable solutions to optimize the industry s supply chain operations and foster long-term growth and competitiveness
Keywords: tannery; interviews; efficiency; sustainability; competitiveness; challenge; opportunity